Pengetahuan Remaja Putri tentang Pemanfaatan Daun Kelor untuk Pencegahan Anemia - Nurbaiti Nurbaiti; Laida Sanilpa Tiwi (3031-8572, 2022)
The prevalence of anemia among children aged 5-12 in Indonesia is 26%, in women aged 13-18 it is 23%. Anemia can be overcome by consuming green vegetables that can prevent and even treat anemia. One of the vegetables that can prevent anemia is Moringa leaves. Moringa leaves have been known throughout the world as a nutritious plant and WHO has introduced Moringa as an alternative food to overcome nutritional problems. anemia. This study uses a descriptive design, this research is at Baiturrahim Jambi Vocational School, the population in this study is all young women at Baiturrahim Jambi Vocational School totaling 139 students, the sample taken in this study using total sampling technique. This research was conducted on January 12, 2022 at SMK Baiturrahim Jambi The results of this study were mostly 15 years old, namely 55 respondents (39.56%), Good Knowledge of 79 (56.83%) and most of the young women did not consume processed foods. Moringa leaves is 84 (60.4%).. The conclusions from this study were that the majority of young women were 15 years old and the knowledge of young women was included in the good category about the use of Moringa leaves for anemia prevention at Baiturrahim SMK Jambi. Suggestions It is hoped that young women can take part in activities that can provide knowledge, especially about health